Peran Administrasi Sekolah dalam Meningkatkan Kualitas Pelayanan Pendidikan di SMPN 1 Gebang - Leni Rohida; Yanto Heryanto; Panji Krisna Pratiansyah (Yayasan Daarul Huda Kruengmane, 2026)
Effective school administration is a key factor in improving the quality of educational services. SMPN 1 Gebang continues to face several challenges, including suboptimal administrative management, limited utilization of information technology, and inadequate coordination among school stakeholders. This community service program aimed to enhance the capacity of school administrative management through training, mentoring, and strengthening coordination among school members. The program was implemented using a participatory approach over two days, consisting of needs assessment, instructional sessions, training on basic digital-based school administration, hands-on mentoring, and evaluation of the program outcomes. The participants included the principal, administrative staff, teachers, and student representatives of SMPN 1 Gebang. The results demonstrated an improvement in the administrative staff's knowledge and skills in managing correspondence, archives, student records, and the use of a basic digital administration system. Furthermore, coordination among educational service providers became more effective, resulting in faster, more organized, and more accurate administrative processes. The program also contributed to greater administrative service efficiency, increased satisfaction among teachers and students with school services, and the development of a more professional and responsive work culture. The outputs of this community service program include enhanced competencies of school administrative personnel, recommendations for strengthening a digital-based school administration system, and the publication of a scientific article as a means of disseminating the program outcomes.